Prefabricated Shelter for Local Community in Khon Kaen, Thailand - Boonyaputthipong, Chumnan (International Journal of Membrane Science and Technology, 2023)
Nowadays, rapid development and growth of the economic and social changed the ways of living in the community. For low-income people, they try to adjust themselves to survive in this changing world. One of the main problems for this group of people is lack of living places. A temporary shelter in a rural area as well as in an urban area is socially a direct solution in responding to their fundamental needs. Based on the study of temporary shelter in Khon Kaen, Thailand, the normal space within the shelter includes multipurpose area and sleeping area with size of 6 sq.m. for each area. This information is used for this study. The idea of the study is to make a low cost prefabricate temporary shelter. The process of the study began with transform the information from previous research to be a prototype one. An architectural drawing is made and discuss with local shop base on the requirement of using local materials, suitable for simple transportation, easy for construction and limited budget. The final prefabrication shelter has been built and installed for checking the problem of building. However, this study showed a few problems that have to be noted such as too many elements that need good organize process for example. Also, the study has found that the prefabricated shelter can be built to suit local need of Khon Kaen city and other parts of Thailand as well. Finally, this prototype can be applied for other function beside a shelter for living. It can be temporary site office, shop, or others.